Harmonizing circumpolar monitoring of Arctic fox: benefits, opportunities, challenges and recommendations. (8th September 2017) - Berteaux, Dominique; Thierry, Anne-Mathilde; Alisauskas, Ray; Angerbjörn, Anders; Buchel, Eric; Doronina, Liliya; Ehrich, Dorothee; Eide, Nina E.; Erlandsson, Rasmus; Flagstad, Øystein; Fuglei, Eva; Gilg, Olivier; et al.
ABSTRACT: The biodiversity working group of the Arctic Council has developed pan-Arctic biodiversity monitoring plans to improve our ability to detect, understand and report on long-term change in Arctic biodiversity. The Arctic fox ( Vulpes lagopus ) was identified as a target of future monitoring because of its circumpolar distribution, ecological importance and reliance on Arctic ecosystems. We provide the first exhaustive survey of contemporary Arctic fox monitoring programmes, describing 34 projects located in eight countries. Monitored populations covered equally the four climate zones of the species' distribution, and there were large differences between populations in long-term trends, multi-annual fluctuations, diet composition, degree of competition with red fox and human interferences. Den density, number of active dens, number of breeding dens and litter size were assessed in almost all populations, while projects varied greatly with respect to monitoring of other variables indicative of population status, ecosystem state or ecosystem function. We review the benefits, opportunities and challenges to increased integration of monitoring projects. We argue that better harmonizing protocols of data collection and data management would allow new questions to be addressed while adding tremendous value to individual projects. However, despite many opportunities, challenges remain. We offer six recommendations that represent decisive progress toward a better integration of Arctic fox monitoring projects. Further, our work serves as a template that can be used to integrate monitoring efforts of other species, thereby providing a key step for future assessments of global biodiversity.